ANALISIS KEMAMPUAN COMPUTATIONAL THINKING SISWA PADA MATERI PERBANDINGAN DI SMP - Edria Al Shahada; Sufyani Prabawanto; Ulfah Nur Azizah (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study examines students’ computational thinking in solving ratio and proportion problems, focusing on decomposition, pattern recognition, abstraction, and algorithm. A qualitative approach was employed involving purposively selected junior high school students. Data were obtained from written tests and interviews, and analyzed through stages of data reduction, data display, and conclusion drawing. The results indicate variations in students’ abilities across all aspects. In decomposition, most students were able to determine known and required information correctly. In pattern recognition, students generally distinguished direct and inverse proportions, although some errors remained. However, difficulties were still palpable in abstraction, particularly in transforming problems into mathematical models, including unit conversions and relationships between variables. In terms of algorithmic thinking, some students were able to organize solution steps systematically, while others were not consistent yet. Overall, decomposition emerged as the most dominant aspect, whereas abstraction was the weakest. These findings suggest the need for learning activities that emphasize mathematical modeling to improve students’ computational thinking skills.